2005
DOI: 10.1097/01.aids.0000183125.93958.26
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of distinct HIV-1 populations in blood monocytes and naive and memory CD4 T cells during prolonged suppressive HAART

Abstract: We observed a cell-specific compartmentalization of the residual virus populations during prolonged suppressive HAART. The coexistence of numerous HIV-1 quasispecies with different resistance genotypes and coreceptor use in cellular reservoirs may be relevant for future antiretroviral treatment strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
59
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(64 citation statements)
references
References 46 publications
(53 reference statements)
5
59
0
Order By: Relevance
“…44 Moreover, the linear correlation between PBLs and monocyte DNA load observed in our study may also suggest a relationship between these reservoirs and a possible infectious refeeding between them, in accord with Garbuglia and coworkers, 14 even though other papers indicated that some patients could harbor genetically distinct HIV-1 quasispecies. 45 In conclusion, this report indicates that effective longterm HAART significantly decreases the HIV-1 DNA load both in PBLs and monocytes in HAART-treated patients compared to naïve individuals. In particular, these results indicate both that PBLs represent the true long-lasting HIV-1 infection reservoir and HAART strongly down-regulates the consistency of monocyte reservoir where HIV-1 DNA load is below the threshold sensitivity of our real time PCR assay in the 65% of two-years HAART-treated patients.…”
Section: Discussionmentioning
confidence: 52%
“…44 Moreover, the linear correlation between PBLs and monocyte DNA load observed in our study may also suggest a relationship between these reservoirs and a possible infectious refeeding between them, in accord with Garbuglia and coworkers, 14 even though other papers indicated that some patients could harbor genetically distinct HIV-1 quasispecies. 45 In conclusion, this report indicates that effective longterm HAART significantly decreases the HIV-1 DNA load both in PBLs and monocytes in HAART-treated patients compared to naïve individuals. In particular, these results indicate both that PBLs represent the true long-lasting HIV-1 infection reservoir and HAART strongly down-regulates the consistency of monocyte reservoir where HIV-1 DNA load is below the threshold sensitivity of our real time PCR assay in the 65% of two-years HAART-treated patients.…”
Section: Discussionmentioning
confidence: 52%
“…Furthermore, we have demonstrated that monocytes can harbor HIV-1 variants that are genetically distinguishable from those present in CD4 ϩ T cells and that HIV-1 in blood monocytes is genetically identical to-or associated with-viral variants found in the blood plasma of patients after receipt of HAART for a prolonged period [16,19,20]. Other investigators have shown similar results for distinct HIV-1 populations in the blood monocytes and CD4 ϩ T cells of patients who received suppressive HAART for a prolonged period [21,22]. Taken together, these studies suggest that HIV-1 circulating in blood monocytes represents the residual replicating HIV-1 that might escape from antiretroviral therapy and might be produced from tissues macrophages [16,19,20,23,24].…”
mentioning
confidence: 79%
“…2). Interestingly, several studies have demonstrated that R5-tropic virus can be isolated from CD4 ϩ T N cells from HIV-infected individuals (15,17,69,70). There are two possible explanations that could account for the discrepancies between in vitro studies and the in vivo observations: (i) HIV-1 infection systematically upregulates CCR5 expression on T N cells, thus making them more susceptible to infection (71)(72)(73)(74), and/or (ii) R5-tropic virus may be more efficiently transferred to T N cells by plasmacytoid dendritic cells (75)(76)(77).…”
Section: Discussionmentioning
confidence: 99%